Frozen elephant trunk versus conventional proximal repair of acute aortic dissection type I - Göbel, Nora; Holder, Simone; Hüther, Franziska; Anguelov, Yasemin; Bail, Dorothee; Franke, Ulrich (Frontiers in Cardiovascular Medicine, 2024)
Objective The extent of surgery and the role of the frozen elephant trunk (FET) for surgical repair of acute aortic dissection type I are still subjects of debate. The aim of the study is to evaluate the short- and long-term results of acute surgical repair of aortic dissection type I using the FET compared to standard proximal aortic repair. Methods Between October 2009 and December 2016, 172 patients underwent emergent surgery for acute type I aortic dissection at our center. Of these, n = 72 received a FET procedure, while the other 100 patients received a conventional proximal aortic repair. Results were compared between the two surgery groups. The primary endpoints included 30-day rates of mortality and neurologic deficit and follow-up rates of mortality and aortic-related reintervention. Results Demographic data were comparable between the groups, except for a higher proportion of men in the FET group (76.4% vs. 60.0%, p = 0.03). The median age was 62 years [IQR (20), p = 0.17], and the median log EuroSCORE was 38.6% [IQR (31.4), p = 0.21]. The mean follow-up time was 68.3 ± 33.8 months. Neither early (FET group 15.3% vs. proximal group 23.0%, p = 0.25) nor late (FET group 26.2% vs. proximal group 23.0%, p = 0.69) mortality showed significant differences between the groups. There were fewer strokes in the FET patients (FET group 2.8% vs. proximal group 11.0%, p = 0.04), and the rates of spinal cord injury were similar between the groups (FET group 4.2% vs. proximal group 2.0%, p = 0.41). Aortic-related reintervention rates did not differ between the groups (FET group 12.1% vs. proximal group 9.8%, p = 0.77). Conclusion Emergent FET repair for acute aortic dissection type I is safe and feasible when performed by experienced surgeons. The benefits of the FET procedure in the long term remain unclear. Prolonged follow-up data are needed.